An Experimental Investigation of the Disparity between WTA and WTP for Lotteries - Stefan Traub; Ulrich Schmidt (Kiel University, Department of Economics, 2006)
In this paper we experimentally investigate the disparity between willingness-to-accept (WTA) and willingness-to-pay (WTP) for risky lotteries. The direction of the income effect is reversed by endowing subjects with the highest price of a lottery when asking the WTP question. Our results show that the income effect is too small to be the only source of the disparity. Since the disparity concentrates on a subsample of subjects, parametric and nonparametric tests of the WTA-WTP ratio may lead to contradictory results. The disparity is significantly reduced when background risk is introduced. That is, putting subjects always into a risky position could improve the contingent valuation method which is often concerned with the assessment of risky situations such as health risks, automobile safety, etc.
Keywords: C91; D81; 330; WTA-WTP disparity; lotteries; background risk; contingent valuation; Willingness to pay; Glücksspiel; Experiment; Theorie